Diversity of the epidemiology of carbapenemase-producing Enterobacteriaceae in long-term acute care rehabilitation settings from an area of hyperendemicity, and evaluation of an intervention bundle. Issue 1 (September 2018) - Arena, F.; Vannetti, F.; Di Pilato, V.; Fabbri, L.; Colavecchio, O.L.; Giani, T.; Marraccini, C.; Pupillo, R.; Macchi, C.; Converti, F.; Rossolini, G.M.
Summary: Background: Long-term acute care rehabilitation facilities (LTACRFs) are affected by carbapenem-resistant Enterobacteriaceae (CRE) in endemic areas. However, the contribution of different subpopulations of patients has not been investigated in these settings. Aim: To study the epidemiology of CRE in an LTACRF, and the effect of an infection control intervention. Methods: A surveillance programme was implemented in a large Italian LTACRF. The intervention included screening for CRE carriage at admission and weekly (for negative patients), and enforcement of contact precautions plus cohorting (in wards and rehabilitation areas) for presumed and confirmed carriers. Prevalence and incidence of CRE colonization and the number of CRE bacteraemias were monitored over one year. Findings: Overall, 1084 patients underwent screening (adherence 89.8%). At admission, 11.6% of patients were colonized, and 9.9% of those negative at admission subsequently became colonized. These percentages were significantly higher among patients with severe brain injuries (SBIs) who were exposed to a higher intensity of care (44.1% vs 8.6% and 63.5% vs 6.8%, respectively). The majority of CRE bacteraemias occurred in the SBI ward. The intervention was associated with a decline in the incidence of CRE colonization in the SBI ward (from 17.7 to 7.2 acquisitions/100 at-risk patient-weeks), but not in other wards. All CRE isolates were Klebsiella pneumoniae carbapenemase-producing K. pneumoniae . Conclusions: A peculiar CRE epidemiology was observed in a LTACRF from Italy, with very high rates of carriage and cross-transmission in SBI patients. A simplified infection control bundle was effective at reducing the incidence of CRE colonization in the SBI ward.